\[\begin{cases} \dfrac{dx}{dt} = 3x - 2y - 3z \\ \dfrac{dy}{dt} = x + 2y - 3z \\ \dfrac{dz}{dt} = x - z \end{cases} \]

\(\)

The general solution to the above differential system is as follows:

\[\begin{cases} x(t) = c_{1}x_{1}(t) + c_{2}x_{2}(t) + c_{3}x_{3}(t) \\ y(t) = c_{1}y_{1}(t) + c_{2} y_{2}(t) + c_{3}y_{3}(t) \\ z(t) = c_{1}z_{1}(t) + c_{2}z_{2}(t) + c_{3}z_{3}(t) \end{cases} \] where
\[ \begin{vmatrix}{x_{j}(t)} \\{y_{j}(t)} \\ {z_{j}(t)} \\ \end{vmatrix} =

\begin{vmatrix}{A_{j}} \\{B_{j}} \\ {C_{j}} \\ \end{vmatrix} * e^{\lambda_{j} t} \]

for \( (1 <= j <= 3) \).

\(\)

If \( C_{1} = 1, \: C_{2} = 1, \: C_{3} = 1 \) and \(x(0) = 1\), \(y(0) = 2\), and \(z(0) = 3 \). Find \( c_{1} + c_{2} + c_{3} \).

\(\)

\(Hint:\) The eigenvalues are \( \lambda_{1} \in \mathbb{R} \) and \( \lambda_{2}, \lambda_{3} = a \pm bi \).

×

Problem Loading...

Note Loading...

Set Loading...